Exercise algebra.manipulation.exponential.equation

Description
solve exponential equation algebraically

Derivation

6*sqrt 3 == 2*9^(1-2*x)
algebra.equations.coverup.times
3*sqrt 3 == 9^(1-2*x)
algebra.manipulation.exponents.factor-as-power
3*sqrt 3 == (3^2)^(1-2*x)
algebra.manipulation.exponents.write-as-power
3*3^(1/2) == (3^2)^(1-2*x)
algebra.manipulation.exponents.mul-exponents
3*3^(1/2) == 3^(2*(1-2*x))
algebra.manipulation.exponents.simple-add-exponents
3^(3/2) == 3^(2*(1-2*x))
algebra.manipulation.exponents.equation.same-base
3/2 == 2*(1-2*x)
algebra.equations.linear.distr-times
3/2 == 2-4*x
algebra.equations.coverup.onevar.minus-right
1/2 == 4*x
algebra.equations.coverup.times
1/8 == x
algebra.equations.linear.flip
x == 1/8